Association between transarterial chemoembolization refractoriness and prognosis in Chinese patients with hepatocellular carcinoma: a large retrospective cohort study - Sun, Qinxue; Wu, Ziliang; Yin, Xi; Li, Feng; Liu, Ri (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) is commonly treated with transarterial chemoembolization (TACE) in intermediate stages. Existing international definitions of TACE refractoriness may not fully suit Chinese patients. The Chinese College of Interventionalists (CCI) proposed a tailored definition, but its impact on HCC prognosis is still limited.MethodsThis study included 844 patients with Barcelona Clinic Liver Cancer (BCLC) stage B HCC from a multicenter dataset. Propensity score matching (PSM) was used to minimize baseline differences between the TACE-Refractoriness (n = 54) and TACE-Non-Refractoriness (n = 108) groups. Kaplan-Meier survival analysis and multivariate Cox regression models were performed to evaluate the association between TACE-Refractoriness and OS. Subgroup analyses were conducted across key clinical and tumor-related characteristics.ResultsKaplan-Meier survival analysis indicated that patients classified as TACE-Refractory exhibited significantly shorter OS compared to those categorized as TACE-Non-Refractory in both the original and matched cohorts (P < 0.001). Furthermore, multivariate analysis identified TACE refractoriness as a significant predictor of poorer OS, yielding an adjusted hazard ratio (HR) of 5.96 (95% CI: 3.39-10.5, P < 0.001). Subgroup analysis further demonstrated the robustness of these findings across subgroups, except in female patients (HR = 3.0, 95% CI: 0.72–12.52; P=0.131).ConclusionsCCI-defined TACE refractoriness is associated with reduced OS in patients with BCLC stage B HCC undergoing TACE.